(untitled) (AmS-Varia, 2016)
In recent years, soapstone research has developed into a multidisciplinary field encompassing a broad range of topics and methodological approaches. Interdisciplinary research now attracts more interest and has contributed significantly to the identification of quarries and understanding of the distribution and use of soapstone. Most collaborative projects have related to certain geographic or thematic areas. As the research on soapstone deposits in Northern Norway illustrates, interdisciplinary work can make important contributions also to other and little explored types of soapstone utilisation. In order to realise the full potential of interdisciplinary research, an expansion of the areas covered and a rethinking of approaches to collaboration and disciplinary compatibility are required. One problem is the use of modern scientific criteria and classification schemes to identify and interpret stone sources, as such methods do not necessarily capture all the aspects of the material that were crucial to past users and production.